Potential Development of Unconventional Oil and Gas Resources in Indonesia: Key Challenges and Future Prospects - Maulana, Rifqi Fajar; Ranaputri, Uray Keisya (Indonesian Journal of Energy, 2024)
The demand for energy is increasing along with the rise in population. Indonesian people rely on conventional resources such as coal, oil, and natural gas to meet their energy needs. It is estimated that coal can only be exploited for up to 61 years, natural gas for 34 years, and oil for 19 years. Meanwhile, Indonesia possesses unconventional oil and gas resources (e.g., coal bed methane (CBM), tight gas, shale gas and oil, and methane hydrate), estimated to reach 1,800 trillion cubic feet (TCF). These resources are in the exploration stage and have yet to be fully exploited due to technological limitations. Nevertheless, the Indonesian government continues to emphasize the development of this type of energy resource. Therefore, this study conducts a review of the potential of unconventional oil and gas resources in Indonesia, covering characteristics, potential occurrences in Indonesia, exploitation methods, utilization as a source of energy, and opportunities and challenges in their application. The method used is a narrative review based on secondary data by examining papers published in reputable national and international journals in the last ten years. Results show that unconventional oil and gas resources have different characteristics, including permeability, porosity, and depth. CBM can be found at the shallowest depth, followed by tight gas, methane hydrate, and the deepest is shale gas. Potential occurrences of these resources in Indonesia include gas hydrate (858.2 TCF), then shale gas (574.07 TCF), coal-bed methane (453.3 TCF), and shale oil 11.24 million tons. Exploitation can be done in various ways, such as dewatering for CBM, hydraulic fracking for tight and shale, and depressurization for methane hydrate. Once exploited, methane gas can be used for power plants, vehicle fuel, and industrial and household needs. Opportunities and challenges from various aspects, as well as applicable laws in Indonesia, are also discussed. In this light, the contribution of our study is to provide a comprehensive review of the characteristics, location, exploitation methods, opportunities, and challenges of utilizing unconventional oil and gas resources in Indonesia.